Solve the equation using the quadratic formula. x^2 + 2x – 3

Question

Solve the equation using the quadratic formula.
x^2 + 2x – 3

in progress 0
Piper 2 weeks 2021-10-07T13:20:38+00:00 2 Answers 0

Answers ( )

    0
    2021-10-07T13:21:42+00:00

    Answer:

    Step-by-step explanation:

    The given quadratic equation is expressed as

    x² + 2x – 3 = 0

    The equation is already in the standard form of ax² + bx + c

    The general formula for solving quadratic equations is expressed as

    x = [- b ± √(b² – 4ac)]/2a

    From the equation given,

    a = 1

    b = 2

    c = – 3

    Therefore,

    x = [- 2 ± √(2² – 4 × 1 × – 3)]/2 × 1

    x = [- 2 ± √(4 – – 12)]/2

    x = [- 2 ± √16]/2

    x = (- 2 + 4)/2 or x = (- 2 – 4)/2

    x = 2/2 or x = – 6/2

    x = 1 or x = – 3

    0
    2021-10-07T13:22:14+00:00

    x²+2x-3

    x²+3x-x-3

    x(x+3)-1(x+3)

    (x+3)(x-1)

    x=-3,1

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )